Diplomasi Digital Menteri Luar Negeri RI pada Konferensi Tingkat Tinggi Group-20 tahun 2021 - M. Yusuf Samad; Diah Ayu Permatasari (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
Utilization of technology by state actors to convey political messages should be able to reach various parties to be involved in digital diplomacy carried out on social media. However, the digital diplomacy of the Indonesian Minister of Foreign Affairs Retno Marsudi through her Twitter account @Menlu_RI has not been able to establish two-way communication and does not involve domestic parties. This study uses a qualitative approach using a social media analysis tool in the form of Foller.me. The results of the study indicate that the delivery of messages on digital diplomacy on the Twitter account @Menlu_RI has not been effective because it does not involve domestic parties and the lack of use of hashtags so that there is no two-way communication. The suggestion for this research is that the digital diplomacy of the @Menlu_RI Twitter account should maximize the use of hashtags and involve domestic parties, especially ministries or officials related to issues or political messages to be conveyed.